The Effect of Surfactant Concentration to Particle Size and Loading Dose of Immunity Jamu’s Ethanolic Extract SNEDDS (Self-Nano Emulsifying Drugs Delivery System) - Dian Eka Ermawati; Samrotul Jannah (Majalah Obat Tradisional, 2023)
Immunity jamu consists of ginger, turmeric, Centella, and cinnamon, that act as immunostimulant agents. However, the infusion is impractical and used a limited dose of the extract, so it is necessary to develop drug delivery to resolve that problem. The SNEDDS technique is expected to increase the solubility, drug release, and absorption of active substances in the body, especially for low solubility of an active substance. SNEDDS consists of oil, surfactant, and co-surfactant. A surfactant is a substance that can reduce surface tension so that emulsion globules form in nanoparticle size. Tween 80 can produce a more transparent solution for oil-in-water emulsions than surfactants with low HLB values. This study aimed to determine the effect of surfactant concentration on the physical properties of SNEDDS to obtain the most loading dose but the smallest particle size. The formula consists of tamanu oil tween 80-propylene glycol of 1:7:1; 1:8:1; and 1:9:1 that incorporated extracts were 75, 150, and 375 mg. The physical tests included transmittance percentage, emulsification time on AGF media, phase separation, and stability test using the cycling test method. SNEDDS, then followed by the Particle Size Analyzer test. The results showed that the greater surfactant concentration produced a better transmittance value, a faster emulsification time, and stability. Formula with oil: surfactant: co-surfactant of 1:8:1 is a system that meets the requirement for immunity jamu with an optimal loading dose and small particle size compared to another formula. The extract’s loading dose of 375 mg has a particle size of 27.17 nm and a polydispersity index of 0.25.